Measuring Structural Economic Vulnerability in Africa - (:unkn) unknown (My University, 2014)
In 2006, at a time when growth had clearly resumed in Africa, the opening speech at the first African Economic Conference organized by the African Development Bank and AERC was entitled “Economic vulnerability, still a challenge for African growth” (Guillaumont 2007, 2008). Eight years on, including a global recession, food and fuel price spikes, and recent state crises in Africa—although in many countries growth has continued—vulnerability remains an issue to be addressed. Both cross-country econometrics and case studies have documented the impact of external, climatic, and political shocks on Africa’s growth, development, and poverty reduction (Ibid.; see also the chapter by Xubei Luo in this book). Although some progress has been recorded in addressing economic vulnerability in Africa, it remains limited; moreover, the scope of vulnerability itself has been changing with the emergence of new--social and environmental—dimensions.Addressing the vulnerability of African economies requires an identification of its sources and determinants, including a conceptual clarification in view of the broadening scope. Section (2) proposes a conceptual framework where structural vulnerability is distinguished from general vulnerability, from physical vulnerability to climate change, and from state fragility as well. Section (3) analyzes the main features and evolution of structural economic vulnerability in Africa on the basis of an economic vulnerability index, highlighting not only higher structural economic vulnerability, but also a slower decline than in other developing economies. It then appears (section 4) that African economic vulnerability is reinforced by higher physical vulnerability to climate change, as shown by a specific index, and that Africa is the continent with the highest proportion of fragile states, suggesting a link between the various forms of vulnerability in Africa. Finally (section 5), measuring the structural vulnerability o
Keywords: African Research